From teacher thinking to teachers and teaching the evolution of a research community - Craig, Cheryl J.; Meijer, Paulien C.; Broeckmans, Jan. (Bingley, U.K. : Emerald, 2013)
This volume covers advances that have occurred in the thirty year existence of the International study association on teachers and teaching (ISATT), the organization that helped transition the study of teacher thinking to the study of teachers and teaching in all of its complexities. This evolution meant that teachers and the act of teaching are no longer exclusively studied from the outside, but from the inside as well. The chapters capture an international paradigm shift that set the course of teaching and teacher education research. The origins of the movement are traced, work of researchers who contributed to the movement is featured, the spread of the movement into new regions is followed, and the future of the international research community that resulted is imagined. Thirteen section editors and the two main editors present the volume by themes, with work from several regions covered in each theme area. Each sub-section includes (1) a representative sample of research conducted historically on a particular topic; (2) a review of what developments have occurred in the interim; and (3) contemporary piece/s of scholarship.
ch. 1. The International study association on teachers and teaching (ISATT) : seeing tracks and making more / Michael Kompf, Frances O'Connell Rust -- ch. 2. The origins of ISATT : an idiosyncratic perspective / Joost Lowyck -- ch. 3. The role of ISATT in the professional development of Barica Marentic Pozarnik / Barica Marentic Pozarnik, Barbara Steh -- ch. 4. Personal practical knowledge : a study of teachers' classroom images / D. Jean Clandinin -- ch. 5. From teacher knowledge to teacher learning in community : transformations of theory and practice / Freema Elbaz-Luwisch, Lily Orland-Barak -- ch. 6. Pedagogical content knowledge : twenty-five years later / Maher Hashweh -- ch. 7. Story-maker, storyteller : narrative structures in curriculum / Sigrun Gudmundsdottir -- ch. 8. Narrative research : from the margins to being heard / Leena Syrjälä, Eila Estola -- ch. 9. Teacher professional development in teaching and teacher education / Beatrice Avalos -- ch. 10. The emergence of research on teachers' professional identity : a review of literature from 1988 to 2000 / Douwe Beijaard, Paulien C. Meijer, Nico Verloop -- ch. 11. The moral matters of teaching : a Finnish perspective / Kirsi Tirri, Auli Toom, Jukka Husu -- ch. 12. In search of the essence of a good teacher : toward a more holistic approach in teacher education / Fred A.J. Korthagen -- ch. 13. Reflective classroom practice : case studies of Hong Kong student teachers at work / Ora W.Y. Kwo -- ch. 14. Teacher education in Brazil / Maria Inês Marcondes -- ch. 15. Reflective practice in the teaching profession : the case of training and research practices in the French community in Belgium / Sephora Boucenna, Evelyne Charlier -- ch. 16. Beyond the reach of leading : exploring the realm of leadership and learning / Michael Schratz -- ch. 17. The new lives of teachers / Christopher Day -- ch. 18. Who I am in how I teach is the message : self-understanding vulnerability, and reflection / Geert Kelchtermans -- ch. 19. Be(com)ing a teacher in challenging circumstances : sustaining commitment or giving up in Portugal? / Maria Assunção Flores -- ch. 20. Teachers dealing with failure in a low socio-economic status school in South Africa / Carola Steinberg -- ch. 21. The necessity of providing guidance for reflection in inservice teacher training programs in Kyrgyzstan / Cholpon Musaeva -- ch. 22. Enhancing and sustaining teacher effectiveness as the 'Trojan Horse' in successful science education in Kenya / Samuel Ouma Oyoo -- ch. 23. Blending traditional and constructivist teaching : how one teacher goes about it in a U.S. middle school mathematics classroom / David R. Goodwin -- ch. 24. School-based instructional research (SBIR) : an approach to teacher professional development in China / Xiao Han, Zhuo Feng -- ch. 25. Engaging India's social history to understand and promote teacher change -- ch. 26. Curriculum reform in a non-threatening collaborative environment : an Indian initiative / Tara Ratnam, Jayshri Kannan -- ch. 27. Changes in research paradigms and their impact on teachers and teacher education : a Finnish case / Anneli Lauriala -- ch. 28. Teacher education that makes a difference : developing foundational principles of practice / John Loughran, Fred A.J. Korthagen, Tom Russell -- ch. 29. The sustainability and nonsustainability of a decade of change and continuity in teacher education / Michal Zellermayer, Edith Tabak -- ch. 30. Two European reflections on professional development in the ISATT community : looking backward, moving forward / Barbara Steh, Marjeta Saric -- ch. 31. Self and community : the impact of ISATT on the professional learning, teaching, and research of members in the Asia-Pacific region / Issa Danjun Ying, Amanda McGraw, Amanda Berry -- ch. 32. Back to the future from a Chinese perspective : a philosophical reconstruction of ideas gleaned from the fifteenth ISATT conference / Xiaohong Yang.
Includes bibliographical references and index.
Print version record
Keywords: International Study Association on Teachers and Teaching -- History; Education -- Teaching Methods & Materials -- General; Teaching skills & techniques; Teaching; Education -- Research -- History